2009
DOI: 10.1097/00054725-200912002-00072
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in utilization of specialist care and medications in inflammatory bowel disease

Abstract: BACKGROUND-Optimization of medical therapy and specialist care for inflammatory bowel disease may reduce morbidity. We sought to characterize racial disparities in utilization of healthcare and medical therapy for IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…The clinical outcomes of this disease in African American [AA] patients have been described through examination of several single-institution studies that have shown that AA patients have an increased likelihood of presentation in the emergency room, and a decreased utilization of routine gastroenterology care, and may have an increased frequency of surgical management. [2][3][4] Indications for surgery in CD include perforation, enteric fistula, bleeding, malnutrition and obstruction. Typically, management of these conditions can be controlled through either outpatient or inpatient medical management, which often then allows for a planned elective procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical outcomes of this disease in African American [AA] patients have been described through examination of several single-institution studies that have shown that AA patients have an increased likelihood of presentation in the emergency room, and a decreased utilization of routine gastroenterology care, and may have an increased frequency of surgical management. [2][3][4] Indications for surgery in CD include perforation, enteric fistula, bleeding, malnutrition and obstruction. Typically, management of these conditions can be controlled through either outpatient or inpatient medical management, which often then allows for a planned elective procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This level of expenditure detail is especially important in a disease such as IBD where a wide range of services and treatments and associated costs exist, potentially revealing patterns that total expenditure figures alone fail to capture. 8,11,13 Using nationally representative data from 1996 to 2011, we determined that mean inpatient expenditures composed the highest proportion of IBD direct costs, above outpatient, emergency, office-based, and prescribed medicine costs. When IBD patients were stratified by insurance status, we found that publicly insured patients spent over double the mean expenditures of privately insured or uninsured patients, with differences of $10K and $13K, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Black patients utilized less ambulatory care, specialists, and biologics than whites, while exhibiting increased hospitalization rates. [10][11][12][13] Race-related health disparities have also been demonstrated in IBD disease phenotype, surgery rates, type of surgery, perianal fistulizing disease, and extraintestinal manifestations.…”
Section: ) a Mo N G A L L I B D P A T I E N T S I N P A T I E N Tmentioning
confidence: 99%
“…Black patients utilized less ambulatory care, specialists, and biologics than whites, while exhibiting increased hospitalization rates. [10][11][12][13] Race-related health disparities have also been demonstrated in IBD disease phenotype, surgery rates, type of surgery, perianal fistulizing disease, and extraintestinal manifestations. 2,14 Lower income was associated with higher rates of CD-related surgery along with higher IBD-related hospitalizations, emergency department (ED) visits, and physician visits.…”
mentioning
confidence: 99%